Sosialisasi Infografis Kesehatan Gigi dan Mulut Pada Masa Pandemi di Kelurahan Sungai Ulin - Juliyatin Putri Utami; Galuh Dwinta Sari; Haluanry Doane Santoso; Rahmad Arifin (Universitas Lambung Mangkurat, 2021)
An understanding of the importance of maintaining dental and oral health in this pandemic era will determine the overall health of the community in order to avoid exposure to the Covid-19 virus. Communities are required to be able to overcome their own dental problems. The use of infographics in print and electronic media is the most effective way to attract people to want to read and understand the contents of the Importance of Maintaining Dental and Oral Health during the Covid-19 Pandemic for the Community South Kalimantan. This socialization is in the form of a series of activities carried out to socialize the importance of maintaining dental and oral health during a pandemic by guiding the infographics in 2 languages, namely Indonesian and Banjarese. This activity was carried out at Sungai Ulin Health Center, Sungai Ulin Village, North Banjarbaru District, Banjarbaru City with limited counseling participants namely 20 people. The results of community service supported by questionnaire data illustrated the importance of effective communication media in conveying information about the importance of maintaining oral health during a pandemic. Infographic socialization about the importance of maintaining dental and oral health during a pandemic was needed to support the level of public knowledge in maintaining dental and oral health. The knowledge provided could be the basis to be realized in the behavior of daily life and in checking the dentist during a pandemic.